Perancangan dan Pembuatan Website E-commerce pada UD. SMR - Nathania Limarsono; Silvia Rostianingsih; Djoni Haryadi Setiabudi (Jurnal Infra, 2017)
UD. SMR is a business engaged in the sale of tools and technical tools in East Kalimantan. UD. SMR sales process is still using manual system, the buyer must come directly to do selection and ordering goods and to do payments. With the e-commerce website is expected to facilitate the process of 24-hour sales transactions, payments and help promote the latest goods, and provide accurate, complete and clear information about the produts to the buyer.The program was developed and created using PHP and MySQL Programming Languages. System design using data flow diagram, flowchart, and entity relationship diagram. Database created using to create a sales process for buyers, admin, stock reports, sales reports, and delivery reports.From the test results, the program can process sales transaction data and display reports which are related to UD. SMR.